The effects of a life skills-based intervention on emotional health, self-esteem and coping mechanisms in Malaysian institutionalised adolescents: Protocol of a multi-centre randomized controlled trial. (2017) - Mohammadzadeh, Marjan; Awang, Hamidin; K.S., Hayati; Ismail, Suriani
Highlights: Randomized controlled trial of life skills education to improve mental and behavioural health among participants. RCT involving 271 Malaysian institutionalised adolescents from 8 orphanages. More than 30 h education for each of the orphanage in intervention group. The first life skill based intervention in Malaysia. Abstract: The aim of the current study was to determine if a life skills-based intervention programme could improve the emotional health, self-esteem and coping skills of Malaysian institutionalised adolescents. This study was a randomized controlled trial with pre-, post- and four-month follow-up tests comprising intervention and control groups which were randomly selected to receive the intervention programme (life skills education) or the placebo education programme (COMBI programme). Overall, 271 adolescents, who experienced a mild to extra severe score in one of the objectives of the DASS21 questionnaire were selected to participate in the study. The findings of this study can be the starting point of continuous, systematic life skills education for Malaysian children and adolescents, and can be used by researchers and educational planners across the country. Trial registration: TCTR20161010003. Registered on: 6-October- 2016.